Reactive oxygen species generation in aqueous solutions containing GdVO4:Eu3+ nanoparticles and their complexes with methylene blue - Kateryna Hubenko; Svetlana Yefimova; Tatyana Tkacheva; Pavel Maksimchuk; Igor Borovoy; Vladimir Klochkov; Nataliya Kavok; Oleksander Opolonin; Yuri Malyukin (Nanoscale Research Letters, 2018)
Abstract It this letter, we report the study of free radicals and reactive oxygen species (ROS) generation in water solutions containing gadolinium orthovanadate GdVO4:Eu3+ nanoparticles (VNPs) and their complexes with methylene blue (MB) photosensitizer. The catalytic activity was studied under UV-Vis and X-ray irradiation by three methods (conjugated dienes test, OH· radical, and singlet oxygen detection). It has been shown that the VNPs–MB complexes reveal high efficiency of ROS generation under UV-Vis irradiation associated with both high efficiency of OH· radicals generation by VNPs and singlet oxygen generation by MB due to nonradiative excitation energy transfer from VNPs to MB molecules. Contrary to that under X-ray irradiation, the strong OH . radicals scavenging by VNPs has been observed.